Need Analysis for Development ELT Material for the Islamic Education Management Department Students at UIN Alauddin Makassar - Ananda Amalia; Kaharuddin, Kaharuddin; Asmawati, Andi (Universitas islam Negeri Alauddin Makassar, 2023)
This research investigated the need for English for Islamic Education Management Department students at UIN Alauddin Makassar. The researcher involved 44 respondents, 40 students, 1 lecturer, and 3 graduates in this study. A questionnaire and open-ended Questions were employed to collect the data. The findings show that the students' ability levels of all components of English (reading, writing, speaking, listening, grammar, and vocabulary) are at the 'adequate' level. The students prefer to study the components of English sequentially: (1) speaking average (3.44), (2) reading average (3.42), (3) listening average (3.42), (4) vocabulary average (3.42), (5) writing with an average (3.38), and (6) grammar with an average (2.77). The problem experienced by students in learning is a